2017
DOI: 10.1093/annonc/mdx108
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline gut microbiota predicts clinical response and colitis in metastatic melanoma patients treated with ipilimumab

Abstract: Baseline gut microbiota enriched with Faecalibacterium and other Firmicutes is associated with beneficial clinical response to ipilimumab and more frequent occurrence of ipilimumab-induced colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
820
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,007 publications
(859 citation statements)
references
References 42 publications
33
820
1
5
Order By: Relevance
“…Furthermore, the composition of gut microbiome was different between the two groups; Clostridiales were more abundant in responders however Bacteroidales were more frequent in nonresponders [8]. These findings were consistent with Chaput et al results concerning the possible adverse role of initial bacteroidetes colonization [7,8]. On the other hand, it has been demonstrated that tumor immune infiltrates including CD8 + T cells were increased in responders.…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecomsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, the composition of gut microbiome was different between the two groups; Clostridiales were more abundant in responders however Bacteroidales were more frequent in nonresponders [8]. These findings were consistent with Chaput et al results concerning the possible adverse role of initial bacteroidetes colonization [7,8]. On the other hand, it has been demonstrated that tumor immune infiltrates including CD8 + T cells were increased in responders.…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecomsupporting
confidence: 88%
“…Patients having microbiota enriched with Faecalibacterium genus and other Firmicutes had significantly higher progression-free survival (PFS) (p = 0.0039) and overall survival (OS) compared with patients having initial microbiota enriched with bacteroidetes. They also found higher proportion of these bacteria in all patients having overall survival longer than 18 months [7]. In contrast to Vetizou et al findings, patients who had poor clinical response to ipilimimuab presented higher representation of bacteroidetes (mostly bacteroidetes genus).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Some have proposed manipulation of gut microbiota prior to treatment administration to maximize therapeutic efficacy and minimize adverse effects. Fecal transplant is a recognized treatment for antibiotic refractory Clostridium difficile infections and may be utilized for patients undergoing checkpoint inhibitor therapy (11).…”
Section: Host Factors Of Response and Resistancementioning
confidence: 99%